Everyday Phytochemicals for Cancer: Another Look - Sree, V. Gowri; Camarillo, Ignacio; Shree, T. Jeya; Poompavai, S.; Giri, Prgatheiswar; Begum, S. M. Fazeela Mahaboob; Hemalatha, S.; Mittal, Lakshya; Sieni, E.; Madhivanan, S.; Prabakaran, S.; Sundararajan, R. (Highlights on Medicine and Medical Research Vol. 6, 2021)
Phytonutrients or phytochemicals are plant-based ingredients that preserve, protect, and enhance our health and wellness, including cancer-prevention and other pre-emptive actions in our body. They are present in all fruits, vegetables, greens, and herbs. Marine organisms, such as algae, seaweed, and sponge also contain large amount of bioactive compounds/nutrients. They have various health benefits, including antioxidant, anti-cancer, antimicrobial, anti-inflammatory, anti-diabetic, and antibiotic properties. It is great that researchers are exploring the characterization of various traditional plants and plant constituents and marine organisms against a number of cancers, such as lung cancer and cervical cancer. There exists thousands of phytochemicals, which provide notable health benefits. Most spices, fruits and vegetables contain phytochemicals and their nutritional constituents are being intensively studied to evaluate their effects on health and cancer treatment. In this review, the phytochemicals, such as alkaloids, tannins, saponins, steroid, terpenoid, flavonoids, phenolic compounds, etc. in various fruits, medical plants, and marine red algae are discussed.